PERANCANGAN PROTOTIPE GIM VISUAL NOVEL INTERAKTIF UNTUK FSRD UNIVERSITAS TRISAKTI: MULTITAHAP DENGAN INTEGRASI TEKNOLOGI: Designing an Interactive Visual Novel Game Prototype for FSRD Universitas Trisakti: A Multi-Stage Integrating AI Technology - Akkapurlaura; Tommy Hari Prihatanto; Daniel Marlasputra Simbolon (Universitas Trisakti, 2026)
Designing an Interactive Visual Novel Game Prototype for FSRD Universitas Trisakti: A Multi-Stage Integrating AI Technology. In the digital era, effective educational promotion is paramount to attracting prospective students who have become increasingly selective in choosing a university. One innovative approach involves the implementation of interactive visual novel games. This study aims to design an interactive visual novel game prototype as a promotional medium for the Visual Communication Design (DKV) program at the Faculty of Art and Design, Universitas Trisakti. The research employs a Research and Development (R&D) approach consisting of pre-production, production, and post-production stages. Data were collected through qualitative analysis and limited user evaluation involving students and lecturers. The results indicate that the visual novel approach enhances user engagement in understanding curriculum structure and academic experience. The integration of Artificial Intelligence (AI) in asset creation also improves production efficiency. This study contributes to the development of interactive, game-based promotional media in higher education.